"Suddenly we have hope that there is a future": two families' narratives when a child with spinal muscular atrophy receives a new drug. Issue 1 (1st January 2021) - Hjorth, Elin; Lövgren, Malin; Kreicbergs, Ulrika; Sejersen, Thomas; Asaba, Eric
ABSTRACT: Purpose: This study aims to explore negotiations of hope in everyday life for families where a child with spinal muscular atrophy (SMA) has received a new drug treatment. Methods: A narrative design was used, drawing on interviews and participant observations in two families with children with SMA, types 1–2, to situate family experiences of hope in everyday life. Narrative analysis was used on the data. Results: Results are presented as stories, with details about situations and contexts, to illustrate how hope was used by families to reconstruct their own family narratives. Conclusions: Hope was negotiated and struggled with in different ways by different family members, but contributed to each person's own way of dealing with the disease and outlook for the future.